Adhesion of veneering composite to metal-free CAD/CAM materials: Effect of surface conditioning and adhesive resin type - Önügören, Nazik İrem; Demirci, Fatih; Tatar, Numan; Eyüboğlu, Tan Fırat; Özcan, Mutlu (Taylor and Francis Ltd., 2023)
ObjectivesThis study aimed to investigate the adhesion of veneering composite to metal-free computer-aided design/computer-aided manufacturing (CAD/CAM) materials with different compositions after surface conditioning and application of adhesive resins.Materials and MethodsA total of one hundred and sixty specimens were divided into four groups (n = 40) manufactured either from polyetheretherketone (PEEK; KERAstar PEEK), polyetherketoneketone (PEKK; Pekkton), fiber-reinforced composite (FRC; Trinia), or high-impact polymer composite (COMP; Bredent HIPC) CAD/CAM discs. Each group was then randomly subdivided into four different subgroups of adhesive systems (n = 10) as Visiolink (Bredent), Single Bond Universal (3M), G-Premio BOND (GC), and OptiBond Universal (Kerr). The shear bond strength (SBS) of each specimen with veneering composite material was tested with a universal testing machine following thermocycle aging (5000 times). The modes of failure resulting from the tests were determined with scanning electron microscope (SEM), dispersive spectroscopy (EDS), and analytical imaging. The data were statistically analyzed with two-way ANOVA and Bonferroni post hoc tests (alpha = 0.05).ResultsThe highest SBS values among all groups were found for the COMP material (20.28 +/- 2.08 MPa) with OptiBond Universal adhesive, while the lowest for the PEEK material (10.33 +/- 2.47 MPa) with G-Premio BOND. The most common failure mode for the PEEK and PEKK specimens was adhesive failure, for the FRC and COMP groups mixed failures were common.ConclusionsBond strength values of at least 10 MPa were achieved for all tested between metal-free CAD/CAM materials and adhesive resin application.
Keywords: Adhesion; CAD-CAM; Dental Materials; Fiber Reinforced Composite; PEEK; Polyetherether Ketone; Prosthodontics; Veneering Composite